Knowledge and Risk Behaviors Regarding Human Immunodeficiency Virus Transmission among Portuguese Healthcare Students - Carvalho, Bárbara Joana Alvarenga (2023)
Background: Human immunodeficiency virus (HIV), the agent responsible for acquired immunodeficiency syndrome, remains a worldwide public health problem. Therefore, this study aimed to assess Portuguese healthcare students’ knowledge of HIV, identify risk behaviors for HIV transmission, and assess the frequency of HIV testing and its dissemination by general practitioners. Methods: A cross-sectional observational study was conducted using an anonymous questionnaire published online. The questionnaire was administered to Portuguese healthcare students who voluntarily agreed to participate in the study after clarifying its objectives and procedures. Results: Most students were aware of the three main HIV transmission routes; however, 66.3% were unaware of the level A recommendation for HIV screening in adolescents and adults. In addition, 59.6% of the students were never informed by their general practitioner about HIV screening tests or risk behaviors for HIV transmission. Of the sample, 78.9% had never been tested for HIV infection. Of the 74.6% of sexually active students, 82.0% had or had already had unprotected sex (without a condom). Men showed riskier sexual behaviors than women. None of the inquiries reported intravenous drug use, and most students (69.9%) never shared personal objects. Conclusion: General practitioners and awareness campaigns need to alert and disseminate HIV screening tests. Sexual health and risk behaviors should be addressed more frequently in schools to educate this population because prevention is the best strategy against HIV transmission/contraction.